ANALISIS DAN OPTIMALISASI DALAM MENJUAL ”PERSONAL SELLING SKILL IN SALES MAGIC” - Alang, Syamsu (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2009)
Abstract:The factors that most entrepreneurs faced a / businessman is how they can make sale of the interaction product or service offered to buyers or consumers with effective, thus reducing the risk of rejection and failure in sales promotion, especially in getting the sales margins can be expected. Many ways can be done to bring hope to be included in the criteria of success to sell and realize the expected objectives, among others, with ways of being and optimism in sellingKeyword:entrepreneur, sales interaction, criteria for successful selling